Pilot areas are picked for entry-level agri-environment schemes: Ulster Edition - FARMING LIFE REPORTER (Newsletter (Belfast, Ireland : 1962), 2002)
FOUR areas of England have been picked to pilot a new 'broad and shallow' or 'entry level' scheme aimed at delivering more environmentally- friendly farming, a key element of the Government's investment in a sustainable future for the countryside. An extra pounds 500 million will be invested by the Department of Environment, Food and Rural Affairs over the next three years to deliver a sustainable future for farming and the countryside and to implement the core recommendations of the Curry Commission, including the introduction of an entry level scheme. DEFRA has also launched a major review of agri-environment schemes. DEFRA will work with partners at local level to establish the precise boundaries for the pilot areas. This will involve detailed consideration of factors such as farm type, soil type and the availability of environmental data. DEFRA expects to announce final details early next year, subject to European Union approval. Once the precise boundaries are known, farmers in all four areas will be able to apply to take part in the pilot scheme.